2021
DOI: 10.4103/jos.jos_12_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of canine retraction by conventional and corticotomy-facilitated methods

Abstract: OBJECTIVE: The purpose of this split-mouth single-centered, parallel-group, randomized clinical trial was to evaluate the efficiency of corticotomy-facilitated orthodontics in rapid canine retraction. METHODS: The sample consisted of 10 patients (15–25 years old) requiring extraction of the maxillary first premolars with subsequent canine retraction. The patients’ right sides were randomly assigned to either the corticotomy (experimental) or control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Out of the 39 included studies, 33 were RCTs [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], from which 17 had a split-mouth study design [ 34 , 37 , 41 , 45 , 48 , 53 , 55 , 56 , 57 , 58 , 59 , 60 , 62 , 64 , 65 , 66 ] and 6 were CCTs [ 22 , 67 , 68 , 69 , ...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of the 39 included studies, 33 were RCTs [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], from which 17 had a split-mouth study design [ 34 , 37 , 41 , 45 , 48 , 53 , 55 , 56 , 57 , 58 , 59 , 60 , 62 , 64 , 65 , 66 ] and 6 were CCTs [ 22 , 67 , 68 , 69 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies had identified problems with the randomization practices [ 34 , 35 , 36 , 38 , 39 , 40 , 45 , 48 , 49 , 53 , 55 , 65 ]. Twenty-one of the thirty-three included RCTs with a sufficiently stated randomization process [ 37 , 41 , 42 , 43 , 44 , 46 , 47 , 50 , 51 , 52 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 66 ]. In these trials, randomization was performed with coin tosses, computer-generated random numbers, block randomization, or identical, opaque, sealed envelopes to prevent selection bias.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations